Foliar application of Halocnemum strobilaceum improves Chenopodium quinoa growth and physiological traits for saline agricultural residence - Aljeddani, Ghalia S.; Fakhry, Amal M.; Almoshadak, Ameina S.; Toto, Soliman M. (Frontiers in Plant Science, 2025)
Salinity is a major abiotic stress limiting crop productivity, particularly in arid and semi-arid regions. This study assessed the effectiveness of Halocnemum strobilaceum extract (HE) as a foliar biostimulant to improve growth, yield, and physiological performance of Chenopodium quinoa (quinoa) under NaCl-induced salinity stress (0–150 mM). Elevated salinity significantly reduced root length (- 17.4%), leaf area (- 44.3%), and seed weight (- 26.4%). HE application mitigated these effects, enhancing leaf area (+8.6%) and the weight of 1000 seeds (+33.9%) under moderate to high salinity. Physiological analysis revealed that HE increased photosynthetic efficiency (Fv/Fo) with improvements of 44.3% at 100 mM and 12.4% at 150 mM NaCl., reduced oxidative damage by lowering H2O2 (up to −32.7%) and malondialdehyde (−39.2%) levels, and increased protein (+25.4%) and lipid content (+24.2% under 0 and by 16.5% under 50 mM NaCl). SDS-PAGE revealed salinity-induced changes in quinoa seed proteins, with loss of specific bands and appearance of two novel bands (43, 30 kDa) in the protein profile of HE-treated salinized quinoa plants under 150 mM NaCl. HE enhances salinity stress tolerance by promoting osmotic adjustment, maintaining membrane integrity, and enhancing antioxidant defenses. The SDS-PAGE results suggest de novo synthesis of stress-related proteins, highlighting HE’s role in modulating quinoa’s proteomic response under high salinity.